2014
DOI: 10.3103/s0003701x1402011x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the dual-axis solar tracking system efficiency via drive power consumption optimization

Abstract: A major drawback with active dual axis solar tracking systems is that the power used by the driving mechanism is often drawn from the output power of the solar panel itself. The net energy gain of the photo voltaic panel is therefore less than its maximum value. This work presents a novel design which uses a three fold strategy to minimize the power consumed by the tracking mechanism whilst maintaining the power out put of the photovoltaic panel near its optimal value. The results reveal that the improved trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The results of the current study showed that the potential of the use of trackers associated with photovoltaic panels should be focused on the economic aspect of the investment. In tropical regions with high rain index or cloudiness, the tracking system might not be as efficient as foreseen (Rambhowan & Oree, 2014). More in-depth studies with much more extended duration are necessary in order to be further specific in recommending the proper panels to be used in rural areas of tropical countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study showed that the potential of the use of trackers associated with photovoltaic panels should be focused on the economic aspect of the investment. In tropical regions with high rain index or cloudiness, the tracking system might not be as efficient as foreseen (Rambhowan & Oree, 2014). More in-depth studies with much more extended duration are necessary in order to be further specific in recommending the proper panels to be used in rural areas of tropical countries.…”
Section: Discussionmentioning
confidence: 99%
“…A key disadvantage with solar tracking systems is that the power used by the driving mechanism is often taken away from the output power of the solar panel, decreasing the net energy gain (Rambhowan & Oree, 2014). Therefore, the present study aimed to propose a solar tracker that could be efficiently used in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…In modern PV modules, small electronic components are used as a part of the modules and are called bypass diodes. These diodes allow the current of un-shaded cells to be bypassed through shaded cells, usually, every module has two or three bypass diodes [16][17][18].…”
Section: Figure1 6 Solar Cells Connected In Seriesmentioning
confidence: 99%
“…A dual-axis solar tracking device was structured utilizing an LDR sensor, DC motors and a microcontroller to make it equipped for the uninterruptible supply of electricity for rural applications [13]. A research team presented a noble design for tracking mechanisms using a three-fold strategy and found that the tracking system shows a power output conversion efficiency of 43.6 % in comparison to fixed-panel [14]. A fixed panel system is less efficient in comparison to a moveable tracking system is the fact it does not rotate as a result at times they are unable to capture the maximum intensity of sunlight.…”
Section: Introductionmentioning
confidence: 99%